ORIENTASI PELANGGAN, ORIENTASI PASAR DAN INOVASI SERTA PENGARUHNYA TERHADAP KINERJA BISNIS HOTEL BERBINTANG TIGA DI INDONESIA - Basuki Rachmat (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
This research was aimed at exploring the influence of marketing strategy with customer orientation, market orientation, and innovation on the business performance in the hotel three-star hotel in Indonesia, the purposes of the research are as follows: 1). to test the influence of the customer orientation on the business performance and market orientation, 4). to test the influence of the market orientation on the business performance and innovation, 5). to test the influence of innovation on the business performance.   The research populations are all the three-star hotels in Indonesia as many as 227 hotels. While the unit of the research sample is three-star hotels in Java, Bali, and Lombok Island with amount 158 hotels and by achieved 107 questionaires of the sample unit (response rate 67.7%) are valid. The respondents are human resource managers, general managers, marketing managers, and financial managers. The data were analyzed by using stuctural equation modelling (SEM), and the AMOS Program which has 4.0 version. Structural Equation Modelling (SEM) is a set of statistical technics enable testing a complex relationship combination simultantly.  The hypothesis tested by regression weight-standardized estimates by comparing p-value method and 5% (a=5%) significance level. The hypothesis is significant if probability value (p-value) is < 5%. The results of the research show that three hypothesis are significant and acceptable and two hypothesis are non significant which have non significant influence customer orientation on the business performance (H1), positive significant influence customer orientation on the market orientation (H2), non significant influence market orientation on the business performance (H3), positive significant influence market orientation on the innovation (H4), and positive significant influence innovation on the business performance (H5) have been found.